Analysis and synthesis of electrostatic focusing and accelerating devices with the help of Kapchinskij-Vladimirskij “microcanonical” beam model - Zubetz, V.N.; Derbilov, V.I.; Nikulin, E.S.; Ostroumov, P.N.; Frolov, O.T.; Yakushev, V.P. (Вопросы атомной науки и техники, 1999)
Due to its simplicity the Kapchinskij-Vladimirskij "microcanonical" beam model (MCB) allows us to receive in a few seconds the results of computation when varying both beam parameters and beam forming devices. The MCB model is very good and useful tool for study of electrostatic forming and accelerating devices. Allowing for essential parameters of intensive beam focusing (current, emittance, configuration of emittance contour in phase space) model gives us correct results for a large part of the beam particles.